2015
DOI: 10.1123/japa.2013-0070
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Physical Activity and Quality of Life Domains Among Older Women

Abstract: This study examined whether the weekly volume and frequency of moderate to vigorous physical activity (MVPA) and light walking (LW) were associated with quality of life (QOL) domains of 1,806 older women from Brazil. The WHOQOL-BREF and WHOQOL-OLD instruments were used to measure QOL, while the weekly volume and frequency of MVPA and LW were assessed by IPAQ. An ordinal logistic regression was used as a measure of association. The weekly volumes of MVPA and LW were associated with several domains of QOL. Highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 0 publications
1
20
0
8
Order By: Relevance
“…Older adults without cancer have exhibited a positive association between light-intensity physical activity and enhanced psychological well-being, social participation, and social relationships [35]. Previous work with colorectal cancer survivors established links between light physical activity and health-related quality of life, including mental health component scores among survivors who reported no moderate-to-vigorous physical activity [9], and physical, role, and social role functioning among female (but not male) colorectal cancer survivors [10].…”
Section: Discussionmentioning
confidence: 99%
“…Older adults without cancer have exhibited a positive association between light-intensity physical activity and enhanced psychological well-being, social participation, and social relationships [35]. Previous work with colorectal cancer survivors established links between light physical activity and health-related quality of life, including mental health component scores among survivors who reported no moderate-to-vigorous physical activity [9], and physical, role, and social role functioning among female (but not male) colorectal cancer survivors [10].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, physical activity is one of the most important resources to improving health and quality of life in older adults, which has been revealed by different studies [6][7][8]. In addition to this, many authors have shown that physical activity improves the functional abilities of older adults [9][10][11] as well as their quality of life [12]. In a combined intervention study of physical activity and cognitive stimulation carried out in a sample of 50 older adults where 44 were women [13], an improvement in the functional abilities and activities of daily living were observed.…”
Section: Introductionmentioning
confidence: 99%
“…Lifestyles that include physical inactivity, a high-fat diet, or tobacco and alcohol consumption have frequently been studied by the scientific community as behaviors that influence the state of health in older adults (Vagetti et al, 2015). It seems that retired and senior volunteers are more protected from the hazards of retirement, physical decline, and inactivity than people of the same age who do not perform volunteer work (Fischer and Schaffer, 1993;Wilson and Musick, 1999).…”
Section: Introductionmentioning
confidence: 99%